Morphologic characterization and evaluation of the national collection of germoplasm of camu camu Myrciaria dubia (H.B.K) Mc Vaugh, of the INIA Loreto-Peru (Scientia Agropecuaria, 2011)
The aim of this study was to characterize and evaluate morphologically the national collection of germplasm INIA camu camu made up of 43 accessions collected in the Loreto region, for conservation and use. The results show that the germplasm of camu camu has high variability and three types of plant architecture (column, intermediate and branched). The flowers are hermaphrodite or androgynous and have herkogamy empowering the outcrossing or cross-pollination. The color of the fruit depends on the state of maturation of the same, varies from green to red-violet, the number of seeds per fruit varies from 1 to 4, the number of fruits per kg is 90 to 148. Twenty one accessions were found with yields greater than 15 kg per plant and 16 accessions of over 2000 mg of ascorbic acid /100 g of pulp. In addition, we identified 10 promising accessions by fruit yield and ascorbic acid contents. Through Principal Component Analysis was determined that the variables are positively associated with the fruit yield, plant height and stem diameter. The dendrogram derived from cluster analysis allowed the identification of three groups based on fruit yield, the first group consists of 22 accessions whose fruit yields are between 2.29 and 11.97 kg / plant, the second group 16 accessions that have yields 16.97 to 30.35 kg of / plant, and the third group consists of 5 accessions from 36.52 to 39.24 yields kg/plant.
Keywords: camu camu; germplasm; accessions; variability; conservation; use.